ARCHITECTURAL DECOR AS A LANGUAGE: AUTHENTICITY AND THE ETHICS OF PRESERVING CULTURAL FORM BASED ON THE PLASTICITY OF WOODEN ORNAMENT TRADITIONS IN BOYKO HERITAGE - Пісьо, Степан; Марусяк, Вікторія (SWorldJournal, 2025)
The decorative elements of Boyko wooden architecture reflect a plastic language of culture, where wood becomes not merely a material, but a carrier of memory, sacred meaning, and socio-cultural identity. Since ancient times, Boyko craftsmen treated wood